2014
DOI: 10.1186/1471-2148-14-85
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive plasticity in the mouse mandible

Abstract: BackgroundPlasticity, i.e. non-heritable morphological variation, enables organisms to modify the shape of their skeletal tissues in response to varying environmental stimuli. Plastic variation may also allow individuals to survive in the face of new environmental conditions, enabling the evolution of heritable adaptive traits. However, it is uncertain whether such a plastic response of morphology constitutes an evolutionary adaption itself. Here we investigate whether shape differences due to plastic bone rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 45 publications
7
111
0
3
Order By: Relevance
“…The plastic changes seen in food hardness studies of mice are typically an overall broadening of muscle attachment points with exposure to hard food types [39,26]. For example, Myers et al [26] found that Peromyscus maniculatus raised on a hard diet in the laboratory had a broader zygomatic plate, similar to our study (Fig 6).…”
Section: Discussionsupporting
confidence: 86%
“…The plastic changes seen in food hardness studies of mice are typically an overall broadening of muscle attachment points with exposure to hard food types [39,26]. For example, Myers et al [26] found that Peromyscus maniculatus raised on a hard diet in the laboratory had a broader zygomatic plate, similar to our study (Fig 6).…”
Section: Discussionsupporting
confidence: 86%
“…These two species occupy different morphospaces along PC2, particularly at mid stages of growth, indicating that differences in the medial part of the occluding edge emerge as the fish grows. stronger, and which have less variation in mandibular shape than those fed soft food (Anderson et al, 2014). Diet also influences the structure of cichlid pharyngeal jaws, with hard food increasing pharyngeal jaw size and molar-like tooth development (Gunter et al, 2013;Gunter and Meyer, 2014;Schneider et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More particularly, foraging and diet consistency have been shown to have a significant impact on the growth and shape remodelling of the mandible as bones respond to their functional environment (Renaud et al 2010;Young and Badyaev 2010). Furthermore, the shift in the shape caused by hard food, requiring a higher bite force, was recently proven to enhance the biomechanical abilities of the mouse jaw and increase its adaptation to its function, i.e., more powerful mastication (Anderson et al 2014). In this sense, it could be that the latitudinal shape trend observed here in the moose reflects a plastic response to a gradient in diet consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Barboza and Bowyer (2000) hypothesized that the sexual segregation in dimorphic ungulates is a consequence of the differing life-histories and energetic needs among males (body and antler growth) and females (gestation and lactation). As the differences in the diet can induce phenotypic changes in the mandible through biomechanical function (Anderson et al 2014), it is possible that the clear differences in the mandible shape between the two sexes reflect their different dietary optimum and foraging behavior (Barboza and Bowyer 2000). An alternative (or additional) process is brought about by the seasonal growth and presence of antlers in males, plausibly affecting the structure of the cranium (Bartosiewicz 1987;Nygrén et al 1992aNygrén et al , 1992b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation